MODEL BIAYA PEMELIHARAAN FASILITAS PADA BANDAR UDARA NGURAH RAI BALI - Dewita, Reni; Adnyana Putera, I G. A.; Putu Suparsa, I G. (JURNAL SPEKTRAN; Vol 1, No 2, Juli 2013, 2013)
Facilities in an airport requires maintenance activity in order to achieve excellent quality level and able to support activities at the airport to avoid negative impacts, which is the declining quality of the facility that can lead to lower levels of the productivity carried out in an airport. Maintenance facilities at Bali's Ngurah Rai airport need the maintenance costs planning. To get proper maintenance actions,  the maintenance costs early stages of planning phase needs to develop a model of facility maintenance costs that can provide the maintenance costs estimates quickly and accurately. To produce a maintenance costs model we should identify the maintenance activities that exist at Ngurah Rai airport. Maintenance costs data used is within the last 5 years (2007-2011). Using the Cost Significant Model methode and the linear regression equation it showed that several of the facility maintenace significantly affect the facility maintenance costs in the Ngurah Rai Airport which is the cost of passenger terminal building maintenance (X 6 ), the cost of runway maintenance (X 1 ), the cost of taxiway maintenance (X 2 ), the cost of air conditioning installation maintenance (X 14 ), the cost of road maintenance (X 4 ), the cost of vehicle parking maintenance (X 5 ), and the cost of navigation and communication equipment maintenance (X 10 ). There is 3  linear regression equation model which is 1) Y = 11873745878,77 + 0,993 X1 + 0,826 X2 + 0,334 X4 + 1,181 X6, 2) Y = -698840481,94 + 1,327 X1 + 1,716 X2 + 5,516 X5+ 3,060 X14, and 3) Y = 82110363478,07 + 1,013 X1 - 17,223X5 + 22,406 X10 - 12,035 X14. After doing the Cost Model Factor (CMF) test to the three linear regression equation, the most accurate equation is linear regression equation Y = 82110363478,07 + 1,013 X1 - 17,223X5 + 22,406 X10 - 12,035 X14 that has the average ratio 0.006% of the actual cost, so it is the best facility maintenance cost model at Bali's Ngurah Rai Airport.
Keywords: Ngurah Rai Airport, maintenance cost estimation, facility maintenance cost model